REHA:real-time IoT-based energy efficient home automation system using ESP8266 and PIR motion sensors - Md. Kamal Ibne Sufian; Poly Bhoumik; Selina Sharmin; Nazma Tara (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
Technological developments have improved living standards, leading to greater demand for home automation based on the internet of things (IoT) concept. This study addresses the limitations of existing home automation systems, which are often costly, complex, and lack energy-saving features. A low-cost IoT-based home automation system is developed using the ESP8266 NodeMCU and PIR motion sensors to enable both remote control and automatic operation of house hold appliances. It uses the Blynk platform for cloud-based monitoring with smart motion-based logic to minimize unnecessary power consumption. The evaluation is conducted through various controlled scenarios and an estimate based energy analysis derived from standard appliance ratings. Experimental results showed a reduction in household energy consumption of about 13–15%. The proposed system offers a cost-effective, practical approach to smart home energy management by combining affordability, automation, and measurable efficiency improvements.